2016
DOI: 10.3390/su8080766
|View full text |Cite
|
Sign up to set email alerts
|

The Asymmetric Effects of Oil Price Shocks on the Chinese Stock Market: Evidence from a Quantile Impulse Response Perspective

Abstract: This paper uses a quantile impulse response approach to investigate the impact of oil price shocks on Chinese stock returns. This process allows us to uncover asymmetric effects of oil price shocks on stock market returns by taking into account the different quantiles of oil price shocks. Our results show that the responses of Chinese stock market returns to oil price shocks differ greatly, depending on whether the oil and stock market is in a bust or boom state and whether the shock is driven by demand or sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…It has been empirically confirmed that the oil price shock is always associated with economic recessions and stock market fluctuations, which may be reflected by either dampened stock returns or aggravated investment risks [20][21][22]. In-depth studies find that the direction and magnitude of such impacts are also leveraged by the states of an economy, for example, whether the economy is developing or developed, which phase of business cycles the economy is in, whether the economy is net importing or exporting oil, and whether the oil price shock is caused by changes from the demand or supply side [23][24][25]. New evidence also shows that the oil shock's impacts on stock markets are most likely to be observed when the stock market is also under an extreme status, for example, financial crisis or contagion from the crisis [26,27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been empirically confirmed that the oil price shock is always associated with economic recessions and stock market fluctuations, which may be reflected by either dampened stock returns or aggravated investment risks [20][21][22]. In-depth studies find that the direction and magnitude of such impacts are also leveraged by the states of an economy, for example, whether the economy is developing or developed, which phase of business cycles the economy is in, whether the economy is net importing or exporting oil, and whether the oil price shock is caused by changes from the demand or supply side [23][24][25]. New evidence also shows that the oil shock's impacts on stock markets are most likely to be observed when the stock market is also under an extreme status, for example, financial crisis or contagion from the crisis [26,27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, oil price changes may have a heterogeneous effect on the stock market comparing different industries. Zhu et al (2016) examined the heterogeneity dependence between crude oil price changes and industry stock market returns in China. The quantile regression result showed that co-movement exists between the global crude oil and Chinese industry markets at low quantiles, while no co-movement exists at other quantiles.…”
Section: Empirical Findingsmentioning
confidence: 99%
“…In this study, the orthogonal rotation method with the largest variance is chosen. 5 Calculate the score of each factor According to the factor scores coefficient matrix and standardized data determined by step 4 , the main factors can be expressed as a linear combination of indicator variables:…”
Section: Model Construction Based On Factor Analysismentioning
confidence: 99%
“…In order to cope with the complicated situation of the international energy market, China must ensure a stable energy system [3]. From an international trade perspective, energy import demand grows rapidly in China [4,5]. Since March 2017, China has become the world's largest importer of crude oil.…”
Section: Introductionmentioning
confidence: 99%